2013
DOI: 10.3350/cmh.2013.19.2.179
|View full text |Cite
|
Sign up to set email alerts
|

A case of peripheral gangrene and osteomyelitis secondary to terlipressin therapy in advanced liver disease

Abstract: Variceal bleeding and hepatorenal syndrome (HRS) are serious and life-threatening complications of advanced liver disease. Terlipressin is widely used to manage both acute variceal bleeding and HRS due to its potency and long duration of action. The most severe (though rare) adverse event is ischemia. The present report describes the case of a patient with gangrene and osteomyelitis secondary to terlipressin therapy. A 71-year-old male with alcoholic liver cirrhosis (Child-Pugh B) and chronic hepatitis C was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…This patient developed severe depletion of natural anticoagulants (antithrombin, 24%; protein C, 20%) in the setting of severe DIC despite not meeting conventional criteria for shock liver. Interestingly, in a previous study reviewing 20 individual case reports of SPG [94], 4 (20%) were noted to have "cirrhosis" [95][96][97][98]. As mentioned earlier, one of the earliest cases of SPG (reported in 1939) occurred in a patient who at autopsy had "cardiac cirrhosis" [5].…”
Section: Chronic Liver Diseasementioning
confidence: 93%
“…This patient developed severe depletion of natural anticoagulants (antithrombin, 24%; protein C, 20%) in the setting of severe DIC despite not meeting conventional criteria for shock liver. Interestingly, in a previous study reviewing 20 individual case reports of SPG [94], 4 (20%) were noted to have "cirrhosis" [95][96][97][98]. As mentioned earlier, one of the earliest cases of SPG (reported in 1939) occurred in a patient who at autopsy had "cardiac cirrhosis" [5].…”
Section: Chronic Liver Diseasementioning
confidence: 93%
“…However, there are case reports of terlipressin causing skin necrosis and gangrene (table 1). 4–22 Nineteen articles reporting a total of 25 patients were analysed. Of these patients, 80% were male and the mean age was 58.88±12.36 years.…”
Section: Discussionmentioning
confidence: 99%
“…Le Moine et al [3] reported the absence of ischaemic complications following high doses of terlipressin (1 mg every 4 hours) administration to a patient with HRS over 2 months. Conversely, gangrenous changes on the toes have been reported to appear on the very first day of terlipressin therapy [4]. Ischaemic events, therefore, are probably independent of the duration of terlipressin therapy.…”
Section: Referencesmentioning
confidence: 98%